Optimum Design of Power System Stabilizer based on Improved Ant Colony Optimization Algorithm - Ruba AL-MulaHumadi; Nizar Hadi Abbas; Mohanad Azeez Joodi (Journal of Engineering, 2018)
This paper presents an improved technique on Ant Colony Optimization (ACO) algorithm. The procedure is applied on Single Machine with Infinite Bus (SMIB) system with power system stabilizer (PSS) at three different loading regimes. The simulations are made by using MATLAB software. The results show that by using Improved Ant Colony Optimization (IACO) the system will give better performance with less number of iterations as it compared with a previous modification on ACO. In addition, the probability of selecting the arc depends on the best ant performance and the evaporation rate.